Metabolic changes following transcatheter bariatric embolotherapy for weight loss in obesity: secondary outcomes from a prospective RCT. (25th November 2020) - Fried, M; Reddy, V.Y; Neuzil, P; Rosen, R; Sramkova, P; Kipshidze, N; Kipshidze, N
Abstract: Background/Introduction: Obesity and its comorbid conditions (i.e. type II diabetes mellitus, atrial fibrillation, coronary artery disease, hypertension, etc...) is a growing burden globally, however, the current treatments (i.e. bariatric surgery, intragasrtic balloons and/or pharmaceutical therapy) pose substantial risks or are contraindicated for various populations. Transcatheter bariatric embolotherapy of left gastric artery by reducing "hunger" hormones from the gastric fundus is a procedure for weight loss that has been growing in prominence over the last several years, however, to date no randomized-controlled trial has been conducted until our study. We studied TBE in a double-blind, sham procedure, first in human RCT of patients (pts) with obesity. Purpose: The purpose of this study was to assess the safety and efficacy of TBE for weight loss in obese patients as well as to evaluate metabolic changes. Methods: After IV propofol, eligible pts (age 21–60; BMI 35–50 kg/m 2 ) were randomized 1:1 to Sham (skin nick & 1 hr wait) or TBE. All pts received Lifestyle Therapy (behavioral and diet education). Study staff following the pts were also blinded to treatment. Blood samples for gastrointestinal hormones were collected in EDTA tubes containing a protease inhibitor cocktail and frozen per local laboratory standards. All collected samples were assessed together in two batches at the end of the study. The hormones analyzed included ghrelin, GIP, GLP-1, Visfatin, resistin, PAI-1 (total), Leptin, and C-Peptide. An Oral Glucose Tolerance Test (OGTT) and a diabetes assay was performed at baseline and at 6- and 12-months post-intervention. Note, while diabetes was an exclusion criterion for this study, pre-diabetes was not. Results: 44 pts were enrolled, of which 40 pts were randomized equally to the groups, with no major complications in either group. TBE demonstrated superior weight loss over the control group at 6- and 12-months post-intervention in both intention-to-treat and per-protocol analyses. At 6 and 12 months, the TBE group demonstrated a clinically meaningful decrease in glucose 1-hour post-fasting by OGTT. GIP levels in the TBE group increased at a mean of 21%, indicative of an improvement in pre-diabetic milieu. Circulating plasma visfatin levels decreased 20% at 6 months and 26% at 12 months in the TBE group indicating a decrease in body fat. C-Peptide levels were noticeably increased in the TBE group at 6 months possibly indicating improvements in insulin sensitivity and beta-cell function. Conclusion(s): TBE is safe and results in clinically significant weight loss and demonstrated a positive effect on glucose homeostasis in pre-diabetic patients. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Endobar Solutions, LLC